Regulation of ige-mediated mast cell degranulation in allergy by geranyl acetophenone - Tan, Ji Wei (2017)
The worldwide prevalence of IgE-antigen-mediated allergic diseases, such as asthma and anaphylaxis, has increased dramatically over the past decades. Mast cells, which play a critical role in IgE-mediated allergy by contributing through its ability to release various proinflammatory mediators during degranulation. 2, 4, 6-trihydroxy-3-geranylacetophenone (tHGA), is an active compound originated from a local shrub known as Melicope ptelefolia. Previous studies demonstrated the potential therapeutic effects of tHGA in murine model of allergic airway inflammation. However, the underlying mechanism of the inhibitory effects of tHGA on mast cell degranulation remains unknown. Therefore, the current study aim is to investigate the in vitro and in vivo inhibitory effects of tHGA on IgE-mediated mast cell degranulation beside exploring its underlying mechanism. Three non-toxic concentrations of tHGA were used to investigate the cell morphology changes and selected key mediators release by DNP-IgE-sensitized RBL-2H3 cells during degranulation process. Apart from that, real time qPCR was used to study the effect of tHGA on gene expression of the mediators’ release. Calcium assay kit was used to determine whether tHGA affects the mast cell activation whereas Western blotting was employed to explore the inhibitory role of tHGA by studying the signaling molecules located along LAT and LAT2 axis signaling pathways. In order to justify the speculated molecular target of tHGA, siRNA was utilized to silence the gene of protein of interest. Finally, in vivo study was carried out to determine tHGA’s pharmaceutical effects in an animal model of anaphylaxis. For the results, pre-treatment of tHGA was able to preserve the cell morphology and actin microfilaments rearrangement challenged by DNP-BSA. This has led to a significant decrease in the release of both selected preformed and de novo synthesis mediators as well as the gene expression of mediators’ release. Within the signalling pathway during IgE-mediated mast cell activation, tHGA was shown to play a major inhibitory role in LAT-PLCγ-MAPK pathway, which involves mainly the role of calcium ions. However, tHGA only plays a partial inhibition in the downstream of LAT2-PI3K pathway. Interestingly, the inhibition tHGA does not affect the activity of Syk tyrosine kinase molecule, which is responsible for the activation of both LAT and LAT2 pathways. This shows that the possible molecular target of tHGA in IgE-mediated mast cell degranulation might be the adapter transmembrane protein LAT. Apparently, LAT-deficient RBL-2H3 cells demonstrated that tHGA was unable to inhibit the IgE-mediated mast cell degranulation process, thus further justified the speculation that LAT is the possible molecular target of tHGA. Finally, tHGA is shown to be effective in the in vivo study where pre-treatment of tHGA was able to significantly decrease the serum mediators level while preserving the morphology of isolated peritoneal mast cells in DNP-BSA challenged Sprague Dawley rats by demonstrating less release of granules into the surrounding environment. As a conclusion, tHGA was shown to play a significant inhibitory effect in IgE-mediated mast cell degranulation both in in vitro and in vivo model. Specifically, tHGA targets the transmembrane LAT during the IgE-mediated mast cell activation.